PEOPLE’S CONSCIOUSNESS IN NAGARJUNA’S POEM: नागार्जुन की कविता में जनवादी चेतना - Agrawal, Reena (International Journal of Research -GRANTHAALAYAH, 2017)
The term democracy is the Hindi version of English democracy, for which the words democracy, democracy, democracy etc. are also used, which means - a mechanism or system in which the people have sovereignty. It is an undeniable truth that economic inequality is the root of all difficulties. Due to this, the world is deranged and frustrated and for this reason, since ancient times in India, mystics dreamed to remove the economic disparity between humans. Democracy is one such vision in which workers, peasants and helpless victims come together to play the role of their true partner. जनवाद शब्द अंग्रेजी के डेमोक्रेसी का हिंदी प्रतिरूप है, जिसके लिए जनतंत्र, लोकतंत्र, लोकशाही आदि शब्दों का भी प्रयोग किया जाता है, जिसका अर्थ है - एक ऐसा तंत्र या व्यवस्था जिसमें जनता की संप्रभुता हो। यह निर्विवाद सत्य है कि आर्थिक विषमता सभी कठिनाइयों की जड़ हैं। इसके कारण संसार विश्रृंखलित एवं कंुठित होता है और इसी कारण भारत में प्राचीन काल से ही मनीषियों ने मानव-मानव के मध्य आर्थिक विषमता को दूर करने का स्वप्न देखा। जनवाद एक ऐसी ही दृष्टि है जिसमें मजदूरों, किसानों, असहाय पीड़ितों को एक जुट कर उनके सच्चे साथी की भूमिका निभाती है।